Economic Incentives for Countertrade - Mirus, Rolf; Yeung, Bernard (Journal of International Business Studies, 1986)
This paper examines countertrade using standard economic theory. We show that in many circumstances countertrade is a rational response transaction costs, information asymmetry, moral hazard-agency problems, and other market imperfections. This paper also integrates countertrade into international business theories. Some preliminary hypotheses, that may be empirically testable after refinement, are developed.